2014
DOI: 10.1177/0003319714529180
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Atrial Fibrillation Survey

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia. The Saudi Atrial Fibrillation Survey registry was designed to provide epidemiological and clinical data on patients with AF. The registry included 400 consecutive patients who met the eligibility criteria. Control of AF at the time of the initial visit was achieved by 211 (52.75%) patients. Cardiovascular risk profile of the patients with AF was smoking 92 (23.5%), hypertension 253 (63.25%), diabetes 192 (48%), and dyslipidemia 173 (44%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In the present data, rate and rhythm control were observed in 68.8% and 12.9% respectively and in line with current evidence. Similarly, Hersi and colleagues (3) observed that the rate control was the commonest management strategy (66.2%), while rhythm control was found in 12% and were in accordance to the present observation. The higher rate of smoking among the Saudi atrial fibrillation survey (23.5% vs. 12.9% in the current data) could be explained by the difference in the sample size or the conservative nature of the present sample.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present data, rate and rhythm control were observed in 68.8% and 12.9% respectively and in line with current evidence. Similarly, Hersi and colleagues (3) observed that the rate control was the commonest management strategy (66.2%), while rhythm control was found in 12% and were in accordance to the present observation. The higher rate of smoking among the Saudi atrial fibrillation survey (23.5% vs. 12.9% in the current data) could be explained by the difference in the sample size or the conservative nature of the present sample.…”
Section: Discussionsupporting
confidence: 91%
“…Serious complications like stroke and peripheral arterial disease may happen from thromboembolism. In the Kingdom of Saudi Arabia, hypertension is the most common risk factor followed by ischemic heart disease and smoking (3). AF is prevalent worldwide; it affects more than six million people in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in concordance with the results of a recent study on Saudi patients. [ 15 ] These findings highlight the urgent needs for health promotion activities in Saudi population that focus on reducing and preventing the modifiable risk factors for stroke and cardiovascular diseases. These health promotion activities should focus on lifestyle modification including physical activities, healthy eating, and weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies were published on the clinical characteristics, management, and cardiovascular risk factors in Saudi patients with AF. [ 14 15 ]…”
mentioning
confidence: 99%
“…In Saudi Arabia, hypertension (HTN) and diabetes are the most common risk factors for AF 6. Valvular heart disease, especially mitral valve disease, is another risk factor for AF observed particularly in developing countries 13. The likelihood of AF increases with structural heart disease.…”
Section: Introductionmentioning
confidence: 99%